Horadam Polynomials and a Class of Biunivalent Functions Defined by Ruscheweyh Operator - Waleed Al-Rawashdeh (International Journal of Mathematics and Mathematical Sciences)
In this paper, we introduce and investigate a class of biunivalent functions, denoted by Hn,r,α, that depends on the Ruscheweyh operator and defined by means of Horadam polynomials. For functions in this class, we derive the estimations for the initial Taylor–Maclaurin coefficients a2 and a3. Moreover, we obtain the classical Fekete–Szegö inequality of functions belonging to this class.